Brief Overview of Approaches and Challenges in New Antibiotic Development: A Focus On Drug Repurposing - Boyd, Natalie K.; Teng, Chengwen; Frei, Christopher R. (Frontiers in Cellular and Infection Microbiology, 2021)
Drug repurposing, or identifying new uses for existing drugs, has emerged as an alternative to traditional drug discovery processes involving de novo synthesis. Drugs that are currently approved or under development for non-antibiotic indications may possess antibiotic properties, and therefore may have repurposing potential, either alone or in combination with an antibiotic. They might also serve as “antibiotic adjuvants” to enhance the activity of certain antibiotics.